2008
DOI: 10.1142/s0219633608004088
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular Charge Transfer and Photoisomerization of the DCM Styrene Dye: A Theoretical Study

Abstract: Structures and properties of the low-lying states in 4-(dicyanomethylene)-2-methyl-6(p-dimethylaminostyryl)-4H-pyran (DCM) have been investigated theoretically. Calculations show that the dimethylamino and dimethylanilino twisted conformations of DCM on the potential energy surface of the first excited state (S-1) have relatively high stabilities and remarkable intramolecular charge transfers (ICT). Both structures can serve as candidates for the red-shifted emissive state in polar solvent. In particular, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 27 publications
3
23
0
Order By: Relevance
“…Indeed, in addition to the two configurational isomers, that is, E and Z , 1 can in principle exist in two conformers, obtained by rotation around the single bond in position 6 on the pyranyl moiety. Thus, depending on the reciprocal position of the two C=C double bonds, four isomers, namely s‐trans ‐( E ), s‐cis ‐( E ), s‐trans ‐( Z ), s‐cis ‐( Z ), can be defined (Figure 3, insets) [11b] . This variety of geometrical structures is of great importance, as it can be assumed that each particular isomer possesses peculiar features and contributes in a different way to the overall properties of 1 in solution.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, in addition to the two configurational isomers, that is, E and Z , 1 can in principle exist in two conformers, obtained by rotation around the single bond in position 6 on the pyranyl moiety. Thus, depending on the reciprocal position of the two C=C double bonds, four isomers, namely s‐trans ‐( E ), s‐cis ‐( E ), s‐trans ‐( Z ), s‐cis ‐( Z ), can be defined (Figure 3, insets) [11b] . This variety of geometrical structures is of great importance, as it can be assumed that each particular isomer possesses peculiar features and contributes in a different way to the overall properties of 1 in solution.…”
Section: Resultsmentioning
confidence: 99%
“…This photoswitching ability would be extremely appealing, as it would not only influence its fluorescence properties, but also disclose new routes for fine tuning the optical properties of the fluorophore. However, among the very large number of examples involving DCM in the literature, only a limited number of qualitative studies have been reported on this phenomenon [10a, 11b, 13] . Moreover, aspects related to the complete conformational isomerism have never been deeply elucidated in experimental studies reported so far, and the conformation has been randomly presented in most reported structures.…”
Section: Introductionmentioning
confidence: 99%
“…To corroborate the experimental Raman spectra of DCM with the possible structural changes during the ICT, we performed TDDFT simulations to find the locally optimized geometries and corresponding Raman spectra. Most of the (TD)DFT studies on DCM or similar push-pull emitters have focused on the evaluation of the absorption and emission spectra which are consistent with the experimental results [27][28][29][30][59][60][61]. Investigation of the vibrational spectrum changes of a molecule during the specific excited state processes may provide important clues to further development for the DFT methods of higher accuracy.…”
Section: Twisted Ict State Of Dcmmentioning
confidence: 88%
“…Despite the wide applications of the ICT process of the "push-pull" emitters, the details of the ICT process including the structural changes were not clearly understood yet. The "twisted" ICT (TICT) state with a perpendicular conformation of the donor group to the molecular plane [23][24][25][26][27] and the "planar" ICT (PICT) [11,13] with the parallel conformation between the donor and acceptor groups have been proposed by numerous theoretical approaches [25,[27][28][29][30]. Millie and co-workers suggested a TICT model with the perpendicularly twisted DMA group for DCM by conformation spectra-intermediate neglect of differential overlap (CS INDO) multi references configuration interaction (MRCI) simulations [28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation